Stratigraphy and Sedimentology of Organic-Rich Limestones of the Chia Gara Formation, Rania Area, Sulaimani, Kurdistan Region, NE Iraq - Mohyaldin, Ibrahim M. J. (Sulaimani Journal for Pure and Applied Sciences, 2007)
The Chia Gara Formation (M.Tithonian-Berriasian) at Rania area is studied in detail stratigraphically and. sedimentologically. The sequence is composed of organic-rich browm to dark shale and organic-rich argillaceous limestones. The shale is dominant in the lower part. The limestone layers becoming lighter in color upward. The upper contact is unconformable with the Balambo Formation. Four types of microfacies have been recognized. Radiolarian wackestone-packestone microfacies are the dominant facies, distributed through the section. The radiolarian moulds replaced by calcite, which indicate a major diagenetic process. The argillaceous limestone beds reveal interested white and dark bands; these structures are recorded for the first time. Thes bands are interpreted to be formed by diffusion process of organic matter-rich solutions through the porous limestone beds. The depositional environment reconstructed from the sedimentological evidences indicates to deep water environment, with warm, quiet water and euxinic condition.
Keywords: Chia Gara Formation; radiolarians; diagenetic process; TOc